Value Of Ultrasound in the Evaluation, Estimation & Assess Relation of Transverse Cerebella Diameter with Fetal Gestational Age Parameters in Normal & Reduced Fetal Growth Fetus - Al hialy, Hadeel Mohamed Farook Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The current research aimed to examine the value of ultrasound in estimation & assess relation between TCD and GA parameters in normal and reduced fetal growth, the study had been done in Mosul city (Iraq) in private ultrasound clinic during the period from 2015 -2019 , and applied on 150 pregnant women ( with normal and reduced fetal growth fetuses) , where the age of pregnant women ranged from 17-37 years , the research continued for the three trimester of gestational age ( 5 -40 weeks ) , cross-sectional approach was applied . Using ultrasound during the research period to measure TCD for pregnant women revealed a correlation between TCD and GA where their relation appeared as linear relationship. The research also proved that the ultrasound technique has a significant value in assess, estimate and evaluate transverse cerebella diameter relation with fetal gestational age and its parameters such as (BPD, FL, HC, AC) . It was also found that there is a positive relation between the transverse cerebral diameter (TCD)  and the other parameter of GA such as BPD, FL, HC, and AC